Ketika Ruang Adat Dinegosiasikan: Politik Pemekaran Banjar Adat Tamblingan menjadi Desa Adat Tamblingan - Sari, Ni Made Kartika; Adhinata, Bayu (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2026)
This study aims to analyze the political process underlying the splitting of the customary territory and the roles of customary actors involved in that process through the Actor-Network Theory (ANT) approach, by mapping the networks of both human and non-human actors and examining the political motives that underpin them. A qualitative research method was employed because it is considered the most appropriate approach for uncovering the deeper meanings embedded in the dynamics of customary politics and complex social interactions, while also enabling the researcher to understand social reality holistically from the perspectives of the actors involved. Data were collected through in-depth interviews with six informants, consisting of the initiator of customary territorial splitting, the former Chief of Munduk Customary Village, the Chair of Team 9 MADT, a representative of MDA Bali, and two community representatives involved in the territorial splitting process, including both supporters of and opponents to the splitting. The findings indicate that this process was shaped by the interests of various actors who drew upon customary legitimacy and ancestral history as sources of justification. Political motives such as material incentives, group solidarity, and an idealistic commitment to the preservation of customary institutions were clearly evident and constituted the primary drivers of the customary territorial splitting. From the perspective of ANT, the territorial splitting occurred through the formation of network consisting human actor (customary leaders, village officials, political elites, and community members) and non-human actor (decrees, historical narratives, and the sacred symbols of Tamblingan). These elements were interconnected in the construction of alliances and legitimacy. Tamblingan, with its spiritual significance, became a powerful symbol mobilized to garner support. Ultimately, the customary territory splitting succeeded not because of the dominance of a single actor, but because this network of interests mutually reinforced one another.